Urinary incontinence, related factors and menopause-related quality of life in mid-aged women assessed with the Cervantes Scale (2012)
Objective: To determine urinary incontinence (UI) prevalence, related factors and menopause-related quality of life (QoL) in mid-aged Colombian women. Methods: A total of 1739 women aged 40–59 were surveyed with the 31 item Cervantes Scale (CS) and a socio-demographic questionnaire. Item 18 of the scale was used to categorize the degree of UI. Remaining 30 items (Adjusted global score) were used to assess global menopause-related QoL. Results: Median age of the sample was 46 years. A 26.0% of women presented some degree of UI, rated as moderate to severe in 16.4% of cases. Adjusted global CS scores (excluding item 18) significantly increased with the severity of UI. Mean scores for item 18 were found to be significantly higher in relation to age, menopausal status, body mass index values, lower education and unemployment status. Multiple linear regression analysis determined that age, postmenopausal status and ethnicity (Mestizo) were significantly related to higher item 18 scores, and thus more severe UI. Conclusion: This is the first study to report UI prevalence in a large mid-aged Latin American female population in which age, menopausal status and ethnicity were related factors.